A critical review of the role of texts in fostering Intercultural Communicative competence in the English Language classroom. (June 2021) - Heggernes, Sissil Lea
Abstract: This review maps and critically evaluates 36 empirical studies from English language teaching (ELT), focusing on the role of texts and activities in intercultural learning. The rationale for this review is the call for theoretically-based recommendations for English language (EL) teachers and researchers on the selection of texts and the design of activities for intercultural learning. It draws on principles from Critical Interpretive Synthesis (CIS), and the studies were gathered from systematic searches of databases, supplemented by manual searches of relevant journals. The results show that fiction texts are more widely used and more strongly rationalized for use than nonfiction texts. There is also a strong focus on dialogic and student-centred activities, and less focus on experiential teaching. It argues that an awareness of the affordances of different text types can assist teachers in mediating EL students' intercultural learning and recommends a greater variety of research and teaching approaches to identify intercultural learning processes. Furthermore, the review calls for more research on intercultural learning in primary and secondary ELT. Highlights: Maps and evaluates 36 empirical studies of English language teaching. Considers texts and activities for intercultural learning. Fiction texts are more widely used and more strongly rationalized for use than nonfiction texts. Awareness of the affordances of different text types can assist teachers in mediating EL students' intercultural learning. A wider variety of research methods are recommended to account for processes of intercultural learning.